2021
DOI: 10.3390/ijerph18168680
|View full text |Cite
|
Sign up to set email alerts
|

One Year of COVID-19 Pandemic in Italy: Effect of Sedentary Behavior on Physical Activity Levels and Musculoskeletal Pain among University Students

Abstract: The COVID-19 outbreak forced Italian students to reduce their daily activities, inducing a seden-tary attitude that was worsened by distanced learning. This study aimed to survey the physical activity levels that were maintained before and during the social restrictions following the pan-demic, their correlation to musculoskeletal pain, as well as analyzing the impact of these COVID-19 restrictions on pain and fatigue that affects daily life activities. A total of 2044 students completed the online questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 52 publications
5
25
1
Order By: Relevance
“…Among 1980 German students, 44.5% saw a decrease from pre-lockdown amounts of physical activity, while 32.8% increased the hours per week of training [ 14 ]. This same pattern was observed in Italian students, for whom physical activity was stratified by volume (high, moderate, low levels and inactivity); after one year of the pandemic, physical activity levels had dropped by 18% and 11% in high and moderate exercisers, respectively, while inactivity increased by 11% [ 15 ]. Children and adolescents, especially those living in urban environments, also showed an important decrease in physical activity levels [ 16 ].…”
Section: Introductionsupporting
confidence: 57%
“…Among 1980 German students, 44.5% saw a decrease from pre-lockdown amounts of physical activity, while 32.8% increased the hours per week of training [ 14 ]. This same pattern was observed in Italian students, for whom physical activity was stratified by volume (high, moderate, low levels and inactivity); after one year of the pandemic, physical activity levels had dropped by 18% and 11% in high and moderate exercisers, respectively, while inactivity increased by 11% [ 15 ]. Children and adolescents, especially those living in urban environments, also showed an important decrease in physical activity levels [ 16 ].…”
Section: Introductionsupporting
confidence: 57%
“…A growing number of studies from the COVID-19 period reported that the limitations imposed by the pandemic lockdown are associated with significant negative changes in physical activity habits [ 55 , 56 ]. Also, eating behaviours and lifestyle were affected by the lockdown, with increased consumption of unhealthy food, which may have a possible negative influence on immune response [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study has more patients in the age group 20-30y followed by 41-50y then 30-40y. The increased neck pain in age 20-30y might be due to COVID-19 restrictions that caused young people to limit and reduce their daily physical activities leading to musculoskeletal pain like MNP [ 32 ].…”
Section: Discussionmentioning
confidence: 99%